2023
DOI: 10.1097/jcma.0000000000000906
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced prognostic value of combined circulating tumor cells and serum carcinoembryonic antigen in patients with colorectal cancer

Abstract: Background: Circulating tumor cells (CTCs) have been investigated as a potential biomarker for predicting prognosis and monitoring therapeutic responses in colorectal cancer (CRC). However, the sensitivity of CTCs detection is low, thus limiting the clinical utility of CTCs. We aim to examine the clinicopathological parameters that improve prognosis prediction for CRC using CTCs as a biomarker. Methods: We enumerated CTCs in 186 CRC patients and associated the number of CTCs with the clinicopathological featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…A study conducted by Yang et al . suggested that the combination of CTCs with the tumor marker CEA has better OS prediction than individual CTCs or CEA and serves as a more effective prediction model in patients with CRC [ 55 ].…”
Section: Methods Of Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Yang et al . suggested that the combination of CTCs with the tumor marker CEA has better OS prediction than individual CTCs or CEA and serves as a more effective prediction model in patients with CRC [ 55 ].…”
Section: Methods Of Detectionmentioning
confidence: 99%
“…A Spanish study carried on 180 metastatic CRC patients receiving first line chemotherapy plus bevacizumab showed that enumeration of CTCs before treatment is a strong and independent prognostic factor for the results of PFS and OS. Thus a change in the number of CTCs during treatment defined 3 groups: patients with a number below 3 have a long PFS and OS; patients with a high number of CTCs before and during Elevated CTC counts at T2 were significantly associated with female sex, vascular invasion, tumor localization in the colon and metastatic lymph nodes [78] 149 patients/immuno nanomagnetic spheres 48.32% (72) > 3 CTCs/7.5 ml Elevated CTC counts were associated with increasing tumor stage and T stage, negative changes in the survival curve and risk curve escalated more rapidly in the CTCs+ group [79] 186 patients/MiSelect R system 37% (69) CTCs count of ≥ 5 as an indicator of worse OS as well as poor prognosis when associated with lower CEA levels, higher CA19-9 levels, and both node status and presence of distant metastasis [55] 218 patients/CellSearch 24% (51) at baseline, 38% (83) at the time of disease progression Great prognosis observed in case of total CTC absence while their presence at any timepoint is associated with a poor prognosis (lower PFS and OS) [80] CEA -carcinoembryonic antigen, CRC -colorectal cancer, CTCs -circulating tumor cells, PFS -progression-free survival, TNM -tumor-node-metastasis treatment have a short PFS and OS; and patients in whom the number converted from high to low have an intermediate result [67]. A Chinese team studied the count of CTCs and the prognosis of patients after platinum-based first line chemotherapy: patients with presence of CTCs suffered from a short DFS after receiving the treatment (p < 0.01) compared to the patients from the CTC-group.…”
Section: Clinical Utility Of Circulating Tumor Cells In Colorectal Ca...mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Distant metastases account for most cancer-related deaths in patients with cancer. 2 Breast cancer exhibits a distinct metastatic pattern, commonly involving the bones, liver, lungs, and brain. 3 The metastasis of cancers, including breast cancer, is a serious problem in clinical tumor therapy.…”
Section: Introductionmentioning
confidence: 99%